VBScript : programmer's reference - Kingsley-Hughes, Adrian (Wrox programmer's references., 2007)
Completely updated for Windows Vista and Windows Server 2003 R2, this book is packed with practical examples for today's programmer, Web developer, or system administratorCombines a comprehensive overview of the VBScript technology and associated technologies with sample code at every stage from beginner to advanced userDiscusses the general syntax, functions, keywords, style, error handling, and similar language-specific topics and then moves into an expanded reference section covering the object models in detailPresents advanced coverage on Active Directory Service Interf.